Convergence in infant mortality rates: the Spanish regions case - Martínez-Asenjo, Cristina; Montañés-Bernal, Antonio (Papeles de Población; Vol. 27 Núm. 109 (2021): Papeles de Población, 2021)
This paper studies the evolution of the infant mortality rates in Spanish regions. Our results allow us to reject the null hypothesis of convergence, but we can find the presence of several convergence clubs, which implies the existence of different patterns of behavior. We also find some degree of connection between the Great Recession and the evolution of the infant mortality rates. The population density, the evolution of the labor market and the percentage of female population that admits having drunk alcoholic beverages in the last two weeks are the factors that help us to explain the forces that drive the creation of the clubs.